Implementasi Model ASSURE dalam Pengembangan Multimedia Berbasis Komputer dan Interaktif Video di Kelas XI SMA - Siti Romlah (Departement of Mathematics Education, 2023)
Education is one way to improve the quality of human resources. The activity of providing learning materials to students so that they can have adequate knowledge and provide benefits in life. The development of science and technology is increasingly encouraging reform efforts in the use of technological results in the learning process. Teachers as educators are required to be able to use technology in the learning process. The learning design developed by the teacher is designed by implementing an ASSURE model in the learning process. The learning design is arranged, arranged, and designed as attractive as possible so as to create a pleasant learning atmosphere for students. Educators also develop learning media using the Powtoon platform. Using computer-based multimedia and video interactive, with the material